Enhanced Depth Imaging Optical Coherence Tomography of Optic Nerve Head Drusen: A Comparison of Cases with and without Visual Field Loss - Traber, Ghislaine L; Weber, Konrad P; Sabah, Mazen; Keane, Pearse A; Plant, Gordon T (Ophthalmology (Rochester, Minn.), 2017)
Enhanced depth imaging (EDI) spectral-domain optical coherence tomography (SD OCT) has been recognized as the most sensitive tool to diagnose optic nerve head drusen (ONHD). The relationship between OCT characteristics and visual loss has not been well documented. This study compares EDI SD OCT-determined morphologic characteristics of drusen in eyes with or without visual field (VF) defects. Descriptive study of patients attending the neuro-ophthalmology service of Moorfields Eye Hospital between January 2013 and October 2014. Patients with diagnosed ONHD and EDI SD OCT imaging of the optic nerve head. Eyes with and without VF defects were compared with regard to retinal nerve fiber layer (RNFL) thickness, drusen morphology, size, extent, visibility on funduscopy, ultrasound, and fundus autofluorescence. Difference in OCT characteristics of ONHD between patients with or without VF defects. Of 38 patients, 69 eyes with ONHD were included. Thirty-three eyes had a normal VF with average mean deviation (MD) -0.96 (±1.2) dB and pattern standard deviation (PSD) 1.6 (±0.3) dB (group I), and 36 eyes had VF defects with MD -13.7 (±10.4) dB and PSD 7.2 (±3.6) dB (group II). Mean global RNFL thickness was 62 (±20.9) μm in the latter group and 99.0 (±12.9) μm in group I. In group I, the predominant drusen type was peripapillary drusen, of variable size. In group II, most eyes had confluent (P < 0.02) and large (>500 μm; P < 0.003) drusen, and drusen were more commonly visible on funduscopy (P = 0.001), ultrasound (P = 0.013), and autofluorescence (P = 0.002). Differences between the 2 groups reached statistical significance in a clustered analysis. RNFL thinning and autofluorescence showed relative sparing of the temporal sector. Sixty-four percent of patients with a VF defect in 1 eye also had a VF defect in their fellow eye. Drusen size and drusen type as classified by OCT morphologic characteristics are significantly different in patients with or without VF defects. Confluent, large, and autofluorescent drusen were more commonly found in patients with VF defects. These findings may assist in clarifying how drusen give rise to visual loss, which is currently not known.